A CLINICAL CASE OF OBSTRUCTIVE SLEEP APNEA IN A 6-YEAR-OLD CHILD - E. A. Abashidze (Вопросы современной педиатрии)
Approximately 25% of children have some problems with sleep, from difficulties with falling asleep to more severe problems, such as apnea. The most common sleep disorder in children is obstructive sleep apnea hypopnea syndrome. The author represents a clinical case of a 6-year old boy with obstructive sleep apnea diagnosed by polysomnography method. The clinical signs of sleep apnea, methods of diagnostics of this disorder and evaluation of treatment efficacy are discussed in the study.